Identification of Risk-Significant Components in Nuclear Power Plants to Reduce Cs-137 Radioactive Risk. (July 2021) - Cho, Jaehyun; Han, Sang Hoon
Highlights: Cs-137 risk quantification using release frequency and Cs-137 radioactivity Identification of all accident scenarios with a Level 1 and 2 PSA linked model Quantification of key risk importance measures using Cs-137 risk Application study on OPR-1000 internal event Level 1 and 2 PSA model Top 20 basic events in FV importance, RRW, and RAW using Cs-137 risk Abstract: The amount and frequency of Cs-137 release in a nuclear accident are regulated to enhance environmental radiation protection. While significant improvements have been accomplished, including the preparation of severe accident mitigation equipment and systems to satisfy Cs-137 regulations, no attempt has yet been made along these lines to manage the structures, systems and components (SSCs) in nuclear power plants. Therefore, this paper proposes a new approach to identify the significant SSCs by quantifying related risk importance measures using release frequency and Cs-137 radioactivity. The new approach includes a Level 1 and Level 2 probabilistic safety assessment (PSA) linked model to obtain the frequency and Cs-137 radioactivity in all accident scenarios. The developed approach was applied to an OPR-1000 full-power internal events PSA model, and as a result, the top 20 SSCs were identified based on Fussell–Vesely importance, risk reduction worth, and risk achievement worth measures. The new approach can support risk-informed management for not only Cs-137 regulations but also public risk by using early and latent cancer fatalities.